2014
DOI: 10.1051/parasite/2014058
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasmosis seroprevalence in wild small rodents, potentially preys of ocelots in north-eastern Mexico

Abstract: The aim of this study was to assess the prevalence of Toxoplasma gondii infection in rodents that coexist with ocelots in north-eastern Mexico. Eighty rodents of five genera were captured and their serum samples tested for specific IgG antibodies to T. gondii by in-house indirect ELISA using three different conjugates. Prevalences of 7% (3/44) and 33% (4/12) were found in Sigmodon hispidus and Liomys irroratus, respectively, and were significantly different. All Baiomys taylori and Oligoryzomys fulvescens were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 19 publications
(27 reference statements)
0
9
0
2
Order By: Relevance
“…Domestic cats are obligate carnivores and annually consume billions of birds and small mammals as prey [ 22 ]. In addition, rodents that coexist with wild felines were found to have high T. gondii infection rates [ 32 ]. Feral cats do not have specific owners and are thus not subjected to prophylactic programs and do not receive treatment against parasites.…”
mentioning
confidence: 99%
“…Domestic cats are obligate carnivores and annually consume billions of birds and small mammals as prey [ 22 ]. In addition, rodents that coexist with wild felines were found to have high T. gondii infection rates [ 32 ]. Feral cats do not have specific owners and are thus not subjected to prophylactic programs and do not receive treatment against parasites.…”
mentioning
confidence: 99%
“…A study from Mexico showed that local rodent species have a relatively important role in the sylvatic cycle of T. gondii. [23]. Another study of urban rodents from Iran shown that 6% of all collected specimens were DNA positive in brain tissue detected by PCR [26].…”
Section: Discussionmentioning
confidence: 99%
“…Antibodies to T. gondii were detected by the complement fixation test in opossums ( D. virginiana ), rock squirrels ( Spermophilus variegatus ), ringtails ( Bassariscus astutus ) and skunks ( Spilogale gracilis ) on a Mexico City natural reserve (Suzan and Ceballos, 2005). In northern Mexico, using an in-house indirect ELISA, antibodies were detected in two wild rodents ( Sigmodon hispidus and Liomys irroratus ) of five species analysed (Rendón-Franco et al ., 2014 c ). Using the latex agglutination test, parasite antibodies were detected in two wild felid species ( Leopardus wiedii and Lynx rufus ), two wild canids ( Canis latrans and Urocyon cinereoargenteus ), a procyonid ( N. narica ) and an opossum ( Didelphis sp.…”
Section: Current Knowledge Of Parasites In Mexican Wildlifementioning
confidence: 99%